1986
DOI: 10.1016/0014-5793(86)81069-9
|View full text |Cite
|
Sign up to set email alerts
|

On the primary site of control in the spontaneous development of small‐intestinal sucrase‐isomaltase after birth

Abstract: We have compared the appearance in the small intestine of baby rabbits, of sucrase and isomaltase activities and of the sucrase-isomaltase mRNA. For the latter we used a cDNA probe encompassing -4.1 kb from the S-end of pro-sucrase-isomaltase cDNA [(1986[( ) Cell 46, 227-2341. Sucrase-isomaltase mRNA and the enzyme activities developed simultaneously from the 15th day after birth onwards. Over two orders of magnitude the enzymatic activities and sucrase-isomaltase mRNA matched one another closely, thus ruling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 30 publications
(11 reference statements)
1
6
0
Order By: Relevance
“…4B), although less well than laetase with its mRNA. This is germane to what we have reported on the site of control of sucrase-isomaltase biosynthesis in rive in fetal life (in man [37]) or during weaning (in rabbits [38]). As pointed out in a previous section, we unexpectedly find in addition a post-translational mechanism that reduces sucrase activity in the proximal third of the small intestine (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…4B), although less well than laetase with its mRNA. This is germane to what we have reported on the site of control of sucrase-isomaltase biosynthesis in rive in fetal life (in man [37]) or during weaning (in rabbits [38]). As pointed out in a previous section, we unexpectedly find in addition a post-translational mechanism that reduces sucrase activity in the proximal third of the small intestine (Fig.…”
Section: Resultsmentioning
confidence: 50%
“…Many different patterns, however, are found. (1) A steady increase after weaning at 14-17 days of life was found with sucrase-isomaltase [4] and IF [5]. (2) A rapid increase at birth, followed by no change until adulthood was seen with the FABPs [6], Although the mRNA levels of the liver FABP rise rapidly at day 1 and are steady for 30 or more days, the tissue levels rise steadily up to 20 days of life [7], Thus, control of liver FABP production, for exam ple, is exercised at the translational level, as well as pre-translationally.…”
Section: Pre-translational Mechanismsmentioning
confidence: 99%
“…Recent studies centred on SI and lactase expression during pre-and post-natal development, during crypt-to-villus cell differentiation in adult animals and in Caco-2 and cells have provided evidence for both transcriptional and posttranslational control sites. In the case of SI, its mRNA and enzyme activity were first detectable, and subsequently increased in parallel during spontaneous or precociously-induced appearance, in newborn rabbits [18] and rats [19] and in human embryos [20], providing evidence for a transcriptional level of regulation. However, Leeper & Henning [19] have suggested that in rats older than 24 days other mechanisms may also be important.…”
Section: Introductionmentioning
confidence: 99%